The Promotional Effect of Ag in Pd‐Ag/Carbon Nanotube‐Graphene Electrocatalysts for Alcohol and Formic Acid Oxidation Reactions. Issue 12 (17th June 2020) - Rajesh, D.; Mahendiran, C.; Suresh, C.
Abstract: Herein, we report the fascinating properties of carbon nanotube‐graphene sheet (CNTs‐GS) as a support matrix for embedded palladium and palladium‐silver (Pd−Ag) nanoparticles. The prepared materials were tested towards small molecule electro‐oxidation reactions. The chemical reduction method is used to incorporate Pd−Ag( x ) nanoparticles ( x wt %=0, 5, 10, 15, 20) on CNTs‐GS surface. The Pd−Ag( x )/CNTs‐GS electro catalysts were characterized by various physicochemical analysis. The catalytic performances of Pd−Ag( x )/CNTs‐GS electrocatalysts were tested towards electrochemical oxidation of alcohols and formic acid. The electrochemical results illustrated that the activity was increased by the addition of Ag on Pd/CNTs‐GS electrocatalyst. The Pd−Ag(10)/CNTs‐GS materials showed excellent performance towards, ethanol, methanol and formic acid oxidations (128.23, 72.26 and 101.02 mA cm −2 ) when compared with Pd/CNTs‐GS (53.54, 33.40 and 45.63 mA cm −2 ) and Pd/C (25.86, 16.93 and 17.32 mA cm −2 ) respectively. The Pd−Ag(10)/CNTs‐GS catalyst showed high stability and resistance to CO poisoning during the oxidation process due to the fact that Ag is an attractive co catalyst and high synergistic interaction existed between silver and palladium. Therefore, the combination of palladium with Ag nanoparticles can be a more favorable for ethanol, methanol and formic acid fuel cell systems. Abstract : Three‐in‐one : A versatile hydrothermal method was adopted for synthesis of Pd−Ag( x )/CNTs‐GS. The morphological study of the electrocatalyst conformed by HR‐SEM and HR‐TEM studies. The Pd−Ag/CNTs‐GS electrocatalyst with various amounts of Ag loaded material was successfully used for electro‐oxidation of alcohols and formic acid. Among the different sets of catalysts, the Pd−Ag(10)/CNTs‐GS electrode materials showed excellent performance towards, ethanol, methanol and formic acid oxidations when compared with Pd/CNTs‐GS and Pd/C catalysts.